Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2020)
A dataset containing 62745 species occurrences available in GBIF matching the query: { "and" : [ { "or" : [ "BasisOfRecord is Observation", "BasisOfRecord is Machine Observation", "BasisOfRecord is Human Observation", "BasisOfRecord is Material sample", "BasisOfRecord is Literature Occurrence", "BasisOfRecord is Specimen" ] }, { "or" : [ "Issue is Geodetic datum assumed WGS84", "Issue is Coordinate reprojected" ] }, "HasCoordinate is true", "TaxonKey is Ascidiacea", "HasGeospatialIssue is false" ] } The dataset includes 62745 records from 180 constituent datasets: 109 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2010. 27 records from Coral Reef Evaluation and Monitoring Project Dry Tortugas 2008. 1 records from Botrylloides crystallinus n. sp., a new Botryllinae Adams & Adams, 1858 (Ascidiacea) from Mediterranean Sea. 28 records from South American Antarctic Marine Biodiversity Literature. 111 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2001. 38 records from Harant H. 1939. The fishery grounds near Alexandria. Ascidiacea (Cartes 1-5). Notes et Memoirs No 28.. 1 records from Collection des données de biodiversité marine de Polynésie française (LAGPLON). 2 records from Canada_BasinMegabenthos2002. 86 records from FBIP:SAEON: Historical Research Survey Database (1897-1949). 109 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2009. 1553 records from Nonindigenous Aquatic Species (NAS) Database Non-freshwater Specimens. 6 records from Type Collection of the Seto Marine Biological Laboratory, Kyoto University. 160 records from Coral Reef Evaluation and Monitoring Project Florida Keys 1998. 1075 records from Royal BC Museum - Invertebrates Collection. 327 records from Bernice P. Bishop Museum. 1 records from Artenvielfalt der Nordsee - Sylt. 3 records from Données naturalistes de Pierre NOEL (Tatihou). 636 records from Geographically tagged INSDC sequences. 5610 records from Données BioObs - Base pour l’Inventaire des Observations Subaquatiques de la FFESSM. 10 records from NORFANZ Biological Survey, Tasman Sea, Australia - New Zealand 2003. 1 records from Invertebrates (Type Specimens) of the Swedish Museum of Natural History. 467 records from DFO Maritimes Research Vessel Trawl Surveys Fish Observations. 29 records from The First Comprehensive Description of the Biodiversity and Biogeography of Antarctic and Sub-Antarctic Intertidal Communities. 180 records from Collection Tunicata SMF. 6 records from Inventaire de l'îlot du Lédénez Vraz. 10 records from Gesamtartenliste Bremerhaven, Helgoland und Sylt. 34 records from Base de datos de la Sala de Colecciones Biológicas de la Universidad Católica del Norte (SCBUCN). 1 records from Non Fish Species Occurrence in ASEAN Region. 17 records from Leptoclinides (Ascidiacea, Didemnidae) from Brazil: new records and two new species. 44 records from COMARGIS: Information System on Continental Margin Ecosystems. 667 records from National Benthic Inventory. 1 records from Texas Tech University - Invertebrate Zoology. 29 records from Centre for Biodiversity Genomics - Canadian Specimens. 27 records from Coral Reef Evaluation and Monitoring Project Dry Tortugas 2007. 44 records from Natural history museum data on Canadian Arctic marine benthos. 489 records from imr_mareano_beamtrawl. 101 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2008. 119 records from BenthosChukchiFN762_1976_Falk5. 12 records from Arctic Ocean Diversity. 38 records from FBIP:IZIKO-UCT:Historical Invertebrates (1930-1980). 2 records from Asia-Pacific Dataset. 39 records from Coral Reef Evaluation and Monitoring Project Dry Tortugas 2011. 160 records from Coral Reef Evaluation and Monitoring Project Florida Keys 1997. 19 records from Invertebrates Collection of the Swedish Museum of Natural History. 140 records from Natural History Museum (London) Collection Specimens. 13 records from University of Amsterdam (NL) – Benthos monitoring of the North Sea research database. 1 records from Macrozoobenthos composition, abundance and biomass in the Arctic Ocean along a transect between Svalbard and the Makarov Basin 1991. 160 records from Coral Reef Evaluation and Monitoring Project Florida Keys 1996. 27 records from Programme national de science participative sur la Biodiversité Littorale (BioLit). 8 records from On the composition of the benthic fauna of the western Fram Strait. 39 records from Coral Reef Evaluation and Monitoring Project Dry Tortugas 2018. 39 records from Coral Reef Evaluation and Monitoring Project Dry Tortugas 2015. 234 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Invertebrates National Collection (MACNIn). 225 records from UAM Invertebrate Collection (Arctos). 4 records from JODC Dataset. 350 records from Classified benthic data for mesophotic organisms and substrates around the Lord Howe Island and Balls Pyramid shelves, southwest Pacific Ocean (2013). 1 records from Shallow-water fauna of Sagami Bay. 32 records from CSIRO, Cruise SS200702, Marine Biodiversity Survey, Southeast Australia, 2007. 2 records from Biodiversity catalog of Marine Coastal Areas of Indigenous People (MCAIPs / ECMPOs), Chile. 272 records from The Deepwater Program: Northern Gulf of Mexico Continental Slope Habitat and Benthic Ecology - DgoMB: Macros. 1846 records from Banco de Datos de la Biodiversidad de la Comunitat Valenciana. 58 records from Marine Biological Sample Database, JAMSTEC. 39 records from Coral Reef Evaluation and Monitoring Project Dry Tortugas 2009. 5668 records from Puerto Rico Long-Term Coral Reef Monitoring Program Database Compilation. 33 records from The Deepwater Program: Northern Gulf of Mexico Continental Slope Habitat and Benthic Ecology - DgoMB: Trawls. 271 records from Canadian Museum of Nature General Invertebrate Collection. 1 records from kerkyra. 24 records from Macrobenthos and Meiobenthos Tuktoyaktuk Harbor and Mason Bay 1985-1988 NOGAP. 7 records from Museum of Comparative Zoology, Harvard University. 1 records from Biological Reference Collections ICM CSIC. 105 records from ZUEC-ASC - Coleção de Ascidiacea do Museu de Zoologia da UNICAMP. 468 records from CSIRO, Cruises, Vertebrate and Invertebrate Fishery Bycatch, North Australia, 1997. 1 records from Schatzinsel Norderney. 160 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2015. 20 records from CSIRO, Benthic Plant Invertebrate and Fish Biodiversity, Great Barrier Reef, Northeast Australia, 2003-2006. 1 records from Archives of the Arctic Seas Zooplankton. 25 records from Coleção de Ascidiacea do Museu Nacional - UFRJ. 39 records from Coral Reef Evaluation and Monitoring Project Dry Tortugas 2013. 160 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2000. 3286 records from Ifremer BIOCEAN database (Deep Sea Benthic Fauna). 2136 records from CAS Invertebrate Zoology (IZ). 160 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2018. 66 records from VIMS Chesapeake Bay Multispecies Monitoring and Assessment Program. 189 records from CSIRO, South East Fishery Habitat Ecosystem Study, Southeast Australia, 1993-1997. 94 records from Atlantic Reference Centre Museum of Canadian Atlantic Organisms - Invertebrates and Fishes Data. 30 records from Macrobenthos Chukchi Sea, 1986. 602 records from Disko Fan Conservation Area in the Davis Strait (Eastern Arctic) - Epibenthic Megafauna Database. 59 records from Galathea II, Danish Deep Sea Expedition 1950-52. 2 records from Insect (HUNM-IN). 6 records from Invertebrate Collection of IBIOMAR (CCT CONICET-CENPAT) (CNP-INV). 1 records from Données DORIS de la FFESSM. 90 records from Marine Invertebrata specimen database of Osaka Museum of Natutal History. 86 records from naturgucker. 1935 records from UF Invertebrate Zoology. 497 records from NaGISA Project. 7 records from MVZ Hildebrand Collection (Arctos). 1 records from Canadian Museum of Nature Mollusc Collection. 33 records from sarce_rockyshores. 160 records from Coral Reef Evaluation and Monitoring Project Florida Keys 1999. 6 records from Kyklades-data of the Central Aegean Sea. 4083 records from iNaturalist Research-grade Observations. 10 records from Zoobenthos data from the Southern Beaufort Sea, 1971-1975. 39 records from Stable isotope data from marine sediment and invertebrates from Davis Station 2009/10. 85 records from ZMMU MSU, White Sea Branch. 628 records from Inventaire des Ascidies de Polynésie française. 24 records from Données naturalistes de Xavier JAPIOT. 3 records from Benthic communities and environmental parameters in three Mediterranean ports (Sardinia, Crete, Tunisia). 574 records from Abundances of benthic invertebrate species in the CEAMARC region 2007/08. 19 records from Marine Benthic Fauna List, Island of Læsø, Denmark. 1 records from Greenland Macrobenthos Young Sound, 1996. 7 records from Données naturalistes d'Anthony DORE. 3 records from imr_mareano_rpsledge. 1313 records from Norwegian Biodiversity Information Centre - Other datasets. 2 records from Canadian Museum of Nature Parasite Collection. 2 records from Données naturalistes de NOËL Rémi. 35 records from BOEM Beaufort Sea, Alaska, Fish and Invertebrate Haul and Catch, with Oceanography, 2008. 28 records from Invertebrates excl. Entomology at the Natural History Museum of Denmark. 39 records from Coral Reef Evaluation and Monitoring Project Dry Tortugas 2014. 12111 records from NMNH Extant Specimen Records. 1196 records from Marine Invertebrate voucher specimens at the Florida Biodiversity Collection, Florida Fish and Wildlife Conservation Commission. 139 records from Collection des données de biodiversité marine de Nouvelle-Calédonie. 1 records from Zukünftiges NSG Höftland/Bockholmwik. 19 records from Insect (MNHM-IN). 13 records from Pyura (Tunicata: Ascidiacea: Pyuridae) on the coasts of Panama. 11 records from Ascidians Specimens of Akita Prefectural Museum. 3310 records from Artportalen (Swedish Species Observation System). 180 records from Norwegian Species Observation Service. 360 records from Northern Territory Museum and Art Gallery provider for OZCAM. 52 records from BIOMAERL.Maerl Biodiversity.Functional Structure And Antropogenic Impacts (1996-1998).. 99 records from IZIKO: Marine Invertebrate Collection (1900-2011). 104 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2002. 498 records from imr_mareano_grab. 31 records from Colección de Zoología Invertebrados - Otros invertebrados. 87 records from Weddell Sea macrozoobenthos EASIZ I. 1 records from Deep-sea ascidians from Papua New Guinea. 195 records from Aportación al conocimiento de la fauna de Ascidias del litoral Pacífico de México. 1390 records from Programme CARTHAM: Inventaire biologique dans le cadre de Natura 2000 en Mer. 12 records from A large marine Caribbean mushroom field: description of Eudistoma amanitum sp. nov. (Ascidiacea: Polycitoridae). 7 records from Données naturalistes d' Anne PROUZET. 1 records from Tauchen und Meer 02. 94 records from Ocean Genome Legacy Collection. 3 records from Grand Manan Basin Benthos. 1 records from Antarctic Marine Species Sequence Data. 103 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2007. 2 records from Données naturalistes hors Île-de-France saisies dans Cettia-idf. 1 records from Las colecciones del Museu Valencià d'Història Natural. 4 records from BIOLOGICAL SCIENCES DATA. 34 records from Further investigations of the effects of the Nella Dan oil spill 1988/94. 149 records from CSIRO, Cruise SS200510, Benthic Biodiversity, Western Australia, 2005. 3 records from BioFokus. 1 records from Arctic benthic invertebrate collection of the Zoological Institute of the Russian Academy of Science. 45 records from Benthos Chirnov Basin 1986 and 2002. 17 records from NW pacific deep-sea benthos distribution and abundance (Beneficial Project). 4 records from Inventaire des Invertébrés marins de la Réserve Naturelle Nationale de Saint-Martin. 356 records from Invertebrate Zoology Division, Yale Peabody Museum. 739 records from Epibionts on Caribbean mangrove roots from Morrocoy National Park and La Restinga Lagoon National Park, Venezuela. 17 records from Inventaire des Ascidies de Guadeloupe et de Martinique. 23 records from Données naturalistes de Pierre NOEL (pnoel). 992 records from International Barcode of Life project (iBOL). 39 records from Coral Reef Evaluation and Monitoring Project Dry Tortugas 2016. 88 records from Auburn University Museum of Natural History Invertebrates. 27 records from Coral Reef Evaluation and Monitoring Project Dry Tortugas 2006. 39 records from Coral Reef Evaluation and Monitoring Project Dry Tortugas 2017. 26 records from New distributional data on ascidian fauna (Tunicata: Ascidiacea) from Mandapam coast, Gulf of Mannar, India. 33 records from CSIRO, Cruise SS200001, Marine Biodiversity, South and Southeast Australia, 2001. 1 records from Invertebrate collection of the Seto Marine Biological Laboratory, Kyoto University. 154 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2017. 52 records from Megabenthos-Epibenthos Greenland. 19 records from Polysyncraton (Ascidiacea, Didemnidae): a re-examination of some specimens and descriptions of three new species. 39 records from Coral Reef Evaluation and Monitoring Project Dry Tortugas 2010. 160 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2016. 64 records from Lund Museum of Zoology (MZLU). 205 records from Données d'occurrences Espèces issues de l'inventaire des ZNIEFF. 14 records from CSIRO, North West Shelf Demersal Marine Resources Study 1980-1997. 34 records from Censo de biodiversidad marina Edo. Miranda. 13 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 9 records from Artenvielfalt der Nordsee - Helgoland. 39 records from Macro- and megafauna from the North Aegean Sea from 1997-1998. 39 records from RNF - Données de l'association Vivarmor Nature. 2 records from Structures and Nutrition Requirements of Macrozoobenthic Communities in the area of the Lomonossov Ridge, 1995-1998. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences